Solar-Powered IoT-Based Soil Temperature and Moisture Monitoring System for Chili Seedling Cultivation - Hasrul Bakri (PT. Global Research Collaboration, 2026)
Chili seedling cultivation requires optimal soil temperature and moisture, but conventional monitoring is inaccurate and lacks real-time capability, especially in off-grid areas. While IoT-based soil monitoring systems have been reported, most rely on grid electricity, lack mobile-based notifications, and are not specifically designed for chili seedlings. This study develops a solar-powered IoT system for real-time monitoring of soil temperature and moisture tailored for chili seedling cultivation. The system integrates an ESP32, DS18B20, soil moisture sensor, and a solar power subsystem (10W panel, 12V 7Ah battery), with Telegram-based alerts. Experimental results (n=10 repetitions per condition, n=15 users for usability) show the system achieves 98.22% accuracy (dry soil) and 95.74% (wet soil), with a mean soil moisture accuracy of 96%. Statistical analysis (paired t-test) reveals a significant difference between dry and wet conditions (p<0.05). System quality based on ISO 25010 shows functionality and portability at 100%, usability at 4.75/5 (very good). The system operates autonomously for 24 hours on solar power, making it suitable for remote agriculture. This study contributes a validated, off-grid, real-time monitoring system with statistical evidence, supporting precision agriculture for chili seedlings.